Implementation of Ginger Tea in Reducing Dysmenorrhea in Nursing Students at the Faculty of Medicine, Mulawarman University - Haliza, Siti Nur; Ramadhani, Siti; Rahayu, Anik Puji; Simarmata, Pratiwi Christa (Fakultas Kedokteran, 2026)
Introduction: Dysmenorrhea, or painful menstruation, is common and can interfere with women's activities. Although painkillers are often used to treat it, they have side effects (Harel, 2006, as cited in Rahayu & Nujulah, 2018). Ginger contains active compounds, such as gingerol and shogaol, that have anti-inflammatory and analgesic properties (Kashefi et al., 2014). The purpose of this study is to determine the effectiveness of ginger tea in reducing the intensity of dysmenorrhea in six nursing students. Methods: The study used a descriptive method with a case study approach. The sample consisted of six nursing students who experienced dysmenorrhea. The intervention was administered during the first three days of menstruation. Pain levels were measured using a Numeric Rating Scale (NRS) before and after the intervention. Results: The results showed a decrease in pain levels after the intervention. On a scale of 0 (no pain) to 10 (extreme pain), the average dysmenorrhea pain level reported by the students before the intervention was between 4 and 8. Conclusion: Providing ginger boiled water proved effective in reducing dysmenorrhea in students. This is due to ginger's gingerol content, which acts as a natural anti-inflammatory and analgesic agent. It can accelerate the healing process of wounds in the uterus caused by the shedding of the uterine wall during menstruationKeywords: Dysmenorrhea, Ginger, Menstruation, Pain